A MODEL SERVPERF IN SURGICAL TREATMENT SERVICES FOR “BPJS” NON ARMY PATIENTS AT THE NAVAL HOSPITAL DR. RAMELAN SURABAYA - Agusta Murphy Tarigan; Agus Subianto; Sudibyo Sudibyo; Lunariana Lubis (JOURNAL ASRO, 2019)
This article discusses national health insurance-based medical services for the community in patient surgery for Social Security Administrator Board (BPJS) non army at the Naval Hospital Dr. Ramelan in Surabaya. The main problem is whether Tangibles factors; Reliability; Responsiveness; Assurance; Empathy; Expertise; Outcome contributed to the surgical treatment of “BPJS” non army patients at the Naval Hospital Dr. Ramelan. The main focus of this analysis is the use of SERVPERF's Services Quality Model to analyze the factors that support and hinder the service of surgery for “BPJS” non army patients at the Naval Hospital Dr. Ramelan. The research was carried out in a descriptive case-based quantitative study with in-depth interview, documentation and questionnaire techniques, to assess service quality class intervals based is used on the mean and standard deviation. The results of the study show that surgical treatment services in 2015-2016 found a tendency of the increasing number of surgery mainly on major surgery and special surgery, because hospitals can respond to public trust in the sense that medical service employees are able to implement excellent services for “BPJS” non army patients so that patients are satisfied with services provided. The findings that still need to be improved are the Assurance factor in line with the development of science and technology as an effort to increase the competitiveness of human resources and the availability of facilities equivalent to international hospitals. Keywords: SERVPERF model, “BPJS” Non Army, Surgical Treatment Services